PRELIMINARY PHYTOCHEMICAL EVALUATION AND SPECTRAL CHARACTERIZATION OF ACTIVE CONSTITUENTS IN THE DRIED EXTRACTS OF THE WHOLE PLANT ARGYREIA IMBRICATA (ROX) SANT AND PATEL - SEBASTIN V,; GOPALAKRISHNAN G,; SREEJITH M,; ANOOB KUMAR KI, (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The present study was designed with the aim of preliminary phytochemical evaluation and spectral characterization phytochemicals present in the extracts of whole plant Argyreia imbricata (Rox) Sant and Patel. Methods: The whole plant A. imbricata was collected, authenticated, and dried in the shade for powdering in mechanical grinder. The powdered plant material was extracted with Soxhlet apparatus using different solvents, and the dried extract obtained was subjected to preliminary phytochemical evaluation, and then column chromatography separation and the separated fractions were subjected to thin-layer chromatography (TLC) separation. Based on the yield in TLC, the selected compounds were subjected to carbon-13 nuclear magnetic resonance, proton NMR (1H NMR), and mass spectroscopic evaluation. Results: In the preliminary phytochemical evaluation, the presence of alkaloids, glycosides, phenolic compounds, flavonoids, carbohydrates, saponins, sterols, and terpenoids was found in different extracts. In column chromatography separation, totally 650 fractions were collected, and four compounds were isolated with the help of TLC. Among the four, two compounds were selected for spectral evaluation based on the yield obtained. The selected compounds were identified and named as, 3-ethyl-5-(hydroxymethyl) phenol and methyl 4-hydroxybenzoate with the help of spectral evaluation. Conclusion: The outcome of this study is beneficial, and further investigation in the future directed toward the detailed pharmacological screening of the extracts may give more valuable results.